Cardiorenal protection with dapagliflozin in patients with type 2 diabetes mellitus and chronic coronary syndrome undergoing percutaneous coronary intervention: a registry cross-sectional study - Zinan Zhao; Naixin Zheng; Tianqi Zhang; Chi Zhang; Yuwei Li; Ming Lan; Ni Zhang; Hui Li; Hu Ai; Deping Liu (Cardiovascular Diabetology)
Abstract Importance Although sodium‒glucose cotransporter-2 (SGLT2) inhibitors have cardiorenal benefits, their efficacy in patients with type 2 diabetes mellitus (T2DM) and chronic coronary syndrome (CCS) undergoing percutaneous coronary intervention (PCI) remains underexplored. Objective To evaluate the cardiorenal protective effects of the SGLT2 inhibitor dapagliflozin in patients with T2DM and CCS receiving PCI. Design, setting, and participants This was a cross-sectional analysis of 1,430 patients from a tertiary hospital database who underwent PCI (January 1, 2018, to March 31, 2022). Main outcomes and measures Cardiac outcomes (PMI/4aMI) and renal outcomes (eGFR and CI-AKI). Results After 1:1 propensity score matching (PSM) (176 dapagliflozin vs. 176 control), the dapagliflozin group showed significantly lower PMI/4aMI rates pre-PSM (39.78% vs. 66.99%; OR 0.862, 95% CI 0.823–0.904; p < 0.001) and post-PSM (39.77% vs. 60.23%; OR 0.660, 95% CI 0.531–0.821; p < 0.001), with sustained significance after adjustment (adjusted OR 0.436, 95% CI 0.285–0.668; p < 0.001). Subgroup analyses highlighted increased protection in patients aged ≥ 65 years, those with multivessel disease, and those with higher contrast volumes. Renal outcomes (CI-AKIESUR and CI-AKIKDIGOs) were not significantly different before or after PSM or after adjustment (all p > 0.05). Conclusions and relevance Dapagliflozin exerted robust cardioprotective effects against PMI/4aMI in patients with T2DM and CCS undergoing PCI, particularly among patients in high-risk subgroups, but it did not significantly reduce the risk of CI-AKI. These findings support the peri-PCI use of dapagliflozin to mitigate cardiac risk while highlighting the need for further research to elucidate its renal effects in this population. Graphical abstract